Towards Discovering New Identity: Transformative Learning Experience as an International Student in Thailand - Somanita Kheang (Adult Education Research Conference, 2022)
This article explores the journey of my studying abroad in Thailand that contributes to my identity changes, including personal and professional development.
Keywords: new identity; Gibbs’ reflective cycle; transformation; international student’s experience; Thailand